Student perception and the efficacy of universities in shaping the entrepreneurial mindset - S. Gubik, Andrea; Bartha, Zoltán (Theory, Methodology, Practice – Review of Business and Management, 2021)
Modern universities may play a significant role in entrepreneurial ecosystems by boosting the entrepreneurial activity of the region. One way to achieve this is through entrepreneurship education. In this study we suggest that one reason why entrepreneurship education has a weak impact on entrepreneurial activity is that the effect of courses and extracurricular programmes depends on how students perceive the entrepreneurial activity. We use the 2018 GUESSS database, which includes 9,667 answers for Hungary, to develop a general linear model. The model suggests that students’ entrepreneurial intentions, attitudes toward entrepreneurship, self-efficacy, social norms, as well as the university, and the field of study all have a small but statistically significant impact on how students perceive the entrepreneurial ecosystem within the university. Our conclusion is that more emphasis on shaping attitudes and arousing student interest can increase the efficiency of entrepreneurship education.